Indirubin-3’-oxime promotes the efficacy of GnRHa in obese-induced central precocious puberty and maintains normal bone growth and body weight via the ERK-Sp1-KISS-1/GPR54 axis: The effects of I3O on central precocious puberty - Jiang, Chunjie; Qi, Lu; Xue, Jiang; Wang, Yibiao (Cellular and Molecular Biology, 2023)
Central precocious puberty (CPP) is a widespread developmental abnormality. The application of gonadotrophin-releasing hormone agonist (GnRHa) is widely useful for the medical therapy of CPP. This study aimed to investigate the combination effect and mechanism of indirubin-3’-oxime (I3O), an active ingredient analogue of traditional Chinese medicine, and GnRHa treatment on the progression of CPP. First, female C57BL/6 mice were fed with a high-fat diet (HFD) for the induction of precocious puberty and treated with GnRHa and I3O alone or in combination. Development of sexual maturation, bone growth and obesity were determined by vaginal opening detection, H&E staining and ELISA. The protein and mRNA expression levels of related genes were evaluated via western blotting, immunohistochemical method and RT-qPCR. Subsequently, tBHQ, an inhibitor of ERK, was applied to verify whether the mechanism of I3O was associated with this signaling. The results showed that the treatment of I3O alone or in combination with GnRHa could alleviate the HFD-induced earlier vaginal opening and serum levels of the gonadal hormone in mice. And, I3O could significantly eliminate the role of growth deceleration of GnRHa in bone development and reversed the side effect of GnRHa on body weight. More importantly, we found that I3O decreased the expression of KISS-1 and GPR54 by suppressing the phosphorylation of ERK1/2 and Sp1 in the hypothalamus in mice. In summary, these data indicated that I3O could promote the efficacy of GnRHa in HFD-induced precocious puberty, and maintain bone growth and body weight in mice via the ERK-Sp1-KISS-1/GPR54 axis.